Oregon Medicaid Expenditures After the 2014 Affordable Care Act Medicaid Expansion: Over-time Differences Among New, Returning, and Continuously Insured Enrollees. Issue 5 (May 2018) - Springer, Rachel; Marino, Miguel; O'Malley, Jean P.; Lindner, Stephan; Huguet, Nathalie; DeVoe, Jennifer E.
Abstract : Background: There is interest in assessing health care utilization and expenditures among new Medicaid enrollees after the 2014 Medicaid expansion. Recent studies have not differentiated between newly enrolled individuals and those returning after coverage gaps. Objectives: To assess health care expenditures among Medicaid enrollees in the 24 months after Oregon's 2014 Medicaid expansions and examine whether expenditure patterns were different among the newly, returning, and continuously insured (CI). Research Design: Retrospective cohort study using inverse-propensity weights to adjust for differences between groups. Subjects: Oregon adult Medicaid beneficiaries insured continuously from 2014 to 2015 who were either newly, returning, or CI. Measures: Monthly expenditures for inpatient care, prescription drugs, total outpatient care, and subdivisions of outpatient care: emergency department, dental, mental and behavioral health, primary care, and specialist care. Results: After initial increases, newly and returning insured (RI) outpatient expenditures dropped below CI. Expenditures for emergency department and dental services among the RI remained higher than among the newly insured. Newly insured mental and behavioral health, primary care, and specialist expenditures plateaued higher than RI. Prescription drug expenditures increased over time for all groups, with CI highest and RI lowest. All groups had similar inpatient expenditures over 24 months post-Medicaid expansion. Conclusions: Our findings reveal that outpatient expenditures for new nonpregnant, non–dual-eligible Oregon Medicaid recipients stabilized over time after meeting pent-up demand, and prior insurance history affected the mix of services that individuals received. Policy evaluations should consider expenditures over at least 24 months and should account for enrollees' prior insurance histories. Abstract : Supplemental Digital Content is available in the text.